PENGUKURAN DAN ANALISA KEPERCAYAAN DAN KEAMANAN DALAM KEPUTUSAN PEMBELIAN ONLINE PRODUK FASHION - Saroso, Dana Santoso; Habiba, Amelia Nimas (Universitas Siber Indonesia, 2024)
The development of digital technology has create a digital marketing models and has changed consumer behavior in doing business transactions. Digital platforms have become a technological medium that is relied upon in E-Commerce. This research uses quantitative methods, which is the population were Shopee users in Mojokerto with 100 respondents. Data analysis techniques in research use descriptive analysis techniques and multiple linear regression. The results of this research show that: (1) Trust influences purchasing decisions, getting a value of 3599 or 72.183%, so shopee is able to create good trust consisting of Achieving results, Acting with Integrity, Demonstrate concern and Benevolence. (2) Security influences purchasing decisions by getting a score of 3118 or 77.86%, so Shopee is able to create good security consisting of Online Privacy, Integrity and Confidentiality. (3) The influence of Trust and Security which is getting higher can increase Purchasing Decisions on the Shopee marketplace in Mojokerto.